2020
DOI: 10.21203/rs.3.rs-24263/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of SMS messaging for diarrhoea measurement: a factorial cross-over randomised controlled trial

Abstract: Abstract Background Text messaging systems are used to collect data on symptom prevalence. Using a text messaging system, we evaluated the effects of question load, question frequency, and financial incentive on response rates and reported infant diarrhoea rates in an infant diarrhoea survey. Methods We performed a factorial cross-over randomised controlled trial of an SMS surveying system for infant diarrhoea surveillance with treatments: financial incentive (yes/no), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] .…”
Section: Uncited Referencesunclassified
“…[1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] .…”
Section: Uncited Referencesunclassified
“…We would expect a lower reported number of diarrhoea episodes with longer recall periods and this was borne out by our analysis including two of the three head‐to‐head comparisons – the exception examined a much smaller gap between questions than the other two [10, 22]. This finding was corroborated by a more recent head‐to‐head comparison where daily recall was associated with a 30 percentage point higher estimated diarrhoea rate than fortnightly recall during a text message survey of under 5 diarrhoea in urban Tanzania [24]. While not examined in our review, it has also been reported that the effect of recall bias is more apparent for moderate diarrhoea compared to severe diarrhoea.…”
Section: Discussionmentioning
confidence: 70%
“…When surveying on health topics, social desirability bias is o en of concern when there is a response which is clearly socially desirable 16,17 . While one may expect assurance of confiden ality (compounded by the inherent privacy of phone interviews) to counteract this, we have demonstrated that this may not be the case 18 . Indeed, Wolter et al (2022) found in Germany that direct ques oning on COVID-19 vaccina on led to a 10pp higher reported vaccina on rate than indirect ques oning using the item count technique 19 .…”
Section: Misalignment Between Vaccina On Intent/report In Hfps and Ac...mentioning
confidence: 67%